The Role of Digital Economy in Iraqi Economic Growth for The Period of 2010-2022 (Analytical Study) - Firas Abdullrada, Maryam; Ali Waheeb, Bushra (Journal of Economics and Administrative Sciences, 2024)
The research addresses the role of the digital economy in the growth of the Iraqi economy during the period from 2010 to 2022. The research is based on the hypothesis that the digital economy has become one of the primary growth drivers worldwide and has a close relationship with economic development. Therefore, the digital transformation in Iraq can accelerate bridging developmental gaps with other countries.It has become evident that the Iraqi economy suffers from structural imbalances for various reasons, hindering economic growth. These reasons include political and economic factors, as well as the absence of a well-thought-out policy to promote the agricultural sector, which is considered one of the fundamental sectors capable of stimulating the Iraqi economy.The study found that the digital economy contributes to increasing the gross domestic product if computer technology and information and communication technology are applied in economic activities such as agriculture, industry, trade, finance, and services. Furthermore, focusing on local expertise and educated individuals can be significant. The study recommends providing the necessary infrastructure for the digital economy in Iraq to serve all sectors, especially the agricultural sector and e-commerce. It also emphasizes the need to promote innovation, reduce corruption, and achieve security stability to create a safe environment for foreign investment. It aims to introduce advanced technology to Iraq and preserve scientific capabilities. Establishing an independent institution to manage and regulate the implementation of the digital economy as a national priority and working on improving information and communication technology is also advised. Paper type: Research paper.